Isolated thrombocytosis with BCR::ABL1 gene rearrangement – a distinct entity or a variant of chronic myelogenous leukemia (CML)? Case report and review of literature - Prajapati, Vipulkumar; Flores, Raina R.; Nooruddin, Zohra I.; Medina, Edward A.; Purnell, Gabriel; Ehman, William; Rodriguez, Juana; Kane, Sheila; Ortega, Veronica; Velagaleti, Gopalrao V.N. (Human Pathology Reports, 2025)
•Isolated thrombocytosis with BCR::ABL1 is rare.•Most cases are asymptomatic.•BCR::ABL1 gene rearrangement is confined to megakaryocytes.•qPCR is most efficient in diagnosis of BCR::ABL1 gene rearrangement.•Timely diagnosis is vital for targeted therapy. Chronic myeloid leukemia (CML) with isolated thrombocytosis and the absence of other significant morphological and/or clinical features of CML poses a diagnostic dilemma. Thrombocytosis in the setting of CML is usually accompanied by significant leukocytosis (usually above 25 K/mcL), prompting testing to detect the disease-defining BCR::ABL1 gene rearrangement, which is present in multiple hematopoietic lineages. In CML cases with isolated thrombocytosis, patients present without symptoms and the thrombocytosis is typically discovered incidentally. In contrast to classic cases of CML, cases with isolated thrombocytosis have shown that the abnormal clone is confined to the megakaryocyte lineage resulting in a normal conventional karyotype and FISH results, if performed on the peripheral blood. Here, we report another case of this rare entity and review the literature. We also suggest that this entity may deserve a separate and distinct entry in the WHO classification of tumors of hematopoietic and lymphoid tissues.